Modified liverpool quick sequential organ failure assessment for prediction mortality amongst hospitalised patients - Mondal, Jeherul Islam; Begum, Rukeya (International Journal of Research in Medical Sciences, 2023)
Background: The aim of this study was to investigate the association between the Low-Quantitative Sepsis-related Organ Failure Assessment (LqSOFA) score and outcomes in pediatric patients with suspected infection. Methods: The study included 100 pediatric patients who presented to the emergency department (ED) with suspected infection. The LqSOFA score was calculated for each patient based on the first set of vital signs and laboratory values obtained in the ED. The primary outcomes of interest were pediatric intensive care unit (PICU) admission, confirmed sepsis, and mortality. Results: The study found that an LqSOFA score of >2 predicted PICU admission with approximately 88% sensitivity and 56% specificity, and confirmed sepsis with 88% sensitivity and 47% specificity. Furthermore, an LqSOFA score of >2 predicted mortality with 94% sensitivity and 48% specificity. The duration of hospital stay also increased with increasing LqSOFA score. Conclusions: The LqSOFA score may be a useful tool for identifying high-risk pediatric patients with suspected infection who may benefit from early intervention. Future studies are needed to validate these findings and determine the optimal threshold for the LqSOFA score in this patient population.